Source localization and sensor placement in environmental monitoring - Khapalov, Alexander (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we discuss two closely related problems arising in environmental monitoring. The first is the source localization problem linked to the question How can one find an unknown ?contamination source?? The second is an associated sensor placement problem: "Where should we place sensors that are capable of providing the necessary" ?adequate data? for that?" Our approach is based on some concepts and ideas developed in mathematical control theory of partial differential equations.
Keywords: source localization; sensor placement; environmental monitoring; controllability; identifiability; parabolic equations